Energy Havesting From Wasted Heat By Using Thermoelectric Generator (TEG) - Nur Ain Binti Zakariya (2023)
This thesis reports the development of simulation on how to harvest energy from wasted heat by using thermoelectric generator. The simulation is run in MATLAB software to show the output of the energy harvesting system by comparing within different model of thermoelectric generator used. The purpose of comparing each result between different models of thermoelectric generator is to study how to optimize the energy harvesting system which one of the objective of the project. The objectives of the project apart from optimization of the energy harvesting system is to design a system that harvest wasted heat and turn it into electricity. The system design is tested in MATLAB software to simulate the output of the design. The development of the simulation is started with study on the mechanism of the thermoelectric itself. It is to understand more on how the electricity can be generated from the wasted heat and take notes on any factor that affecting the efficiency of the system in aspect of the output, industry availability and also cost. The findings show that the best material for thermoelectric generator for daily and common uses is compound of Bismuth and Tellurium or called as Bismuth Telluride. This compound is a semiconductor that can work finely at high temperature of as high as 330 C֯ heat sources continuously and up to 400 C֯ intermittently.